Filsafat Analitik Ludwig Wittgeinstein dan Implikasinya dalam Kajian Agama - Waluyo, Muhammad Edy (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Language is an important part at once inseparable in the life of a human being who was crowned as the homo socius. The presence of languages other than as a tool for expressing the emotions of both empathy, sympathy, praise, invective and so on, is also a tool to develop science, including philosophy. Two theories are built the first Wittgenstein, theory of image, a view which considers the relationship between languages with absolute reality or the world of facts. Second, language games; Descriptive language he thinks is just one form only in the overall use of language. Wittgenstein recommend paths to overcome the problems of philosophy of language by setting the rules of the game for a language with language is a complex language system.